2017
DOI: 10.1152/japplphysiol.01130.2016
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral nasal obstruction affects motor representation development within the face primary motor cortex in growing rats

Abstract: Postnatal growth is influenced by genetic and environmental factors. Nasal obstruction during growth alters the electromyographic activity of orofacial muscles. The facial primary motor area represents muscles of the tongue and jaw, which are essential in regulating orofacial motor functions, including chewing and jaw opening. This study aimed to evaluate the effect of chronic unilateral nasal obstruction during growth on the motor representations within the face primary motor cortex (M1). Seventy-two 6-day-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Previous research demonstrated that oral breathing induces chewing activity (24), but whether the decrease in chewing activity will reduce the bone density of alveolar bones remains unclear. Oral breathing is known to affect craniofacial muscle activity (6,8,9,10). Nonetheless, further studies are needed to explore the relationship between craniofacial muscle activity and the density of alveolar bones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research demonstrated that oral breathing induces chewing activity (24), but whether the decrease in chewing activity will reduce the bone density of alveolar bones remains unclear. Oral breathing is known to affect craniofacial muscle activity (6,8,9,10). Nonetheless, further studies are needed to explore the relationship between craniofacial muscle activity and the density of alveolar bones.…”
Section: Discussionmentioning
confidence: 99%
“…Oral breathing has an important impact on the growth and development of craniofacial structures (1,2,3,4,5). Animal experiments demonstrated that changes in breathing patterns from the nasal cavity to the oral cavity can induce changes in craniofacial muscle activity (6,7,8,9,10,11). Recent studies have focused on the effect of oral breathing on the morphology of maxillofacial (12,13).…”
mentioning
confidence: 99%
“…The functional independence and motor improvements might have alleviated the adverse cerebrovascular effects of OSAS, possibly through enhanced neuroplasticity. A previous study found that unilateral nasal obstruction in rats during growth periods induced changes in arterial SaO 2 % and altered the development of motor representation within the face primary cortex ( 39 ). The greater reduction in alveolar ventilation during REM sleep also resulted in transient declines in SaO 2 % from a sustained level of hypoxia during NREM sleep for OSAS.…”
Section: Discussionmentioning
confidence: 99%
“…In the primary motor cortex mapping study, it was revealed that the change in neuroplasticity due to UNO was a lateral change in the center of gravity of the positive ICMS site (Abe et al, 2017). This is indicative of reorganization of motor expression in the primary motor cortex (Yadav et al, 2003;Abe et al, 2017).…”
Section: Reliability Of the Icms-de Ned Motor Mapsmentioning
confidence: 99%